Condensation of the plasma membrane at the site of T lymphocyte activation. - Gaus, K; Chklovskaia, E; Fazekas de St Groth, B; Jessup, W; Harder, T (2005)
After activation, T lymphocytes restructure their cell surface to form membrane domains at T cell receptor (TCR)-signaling foci and immunological synapses (ISs). To address whether these rearrangements involve alteration in the structure of the plasma membrane bilayer, we used the fluorescent probe Laurdan to visualize its lipid order. We observed a condensation of the plasma membrane at TCR activation sites. The formation of ordered domains depends on the presence of the transmembrane protein linker for the activation of T cells and Src kinase activity. Moreover, these ordered domains are stabilized by the actin cytoskeleton. Membrane condensation occurs upon TCR stimulation alone but is prolonged by CD28 costimulation with TCR. In ISs, which are formed by conjugates of TCR transgenic T lymphocytes and cognate antigen-presenting cells, similar condensed membrane phases form first in central regions and later at the periphery of synapses. The formation of condensed membrane domains at T cell activation sites biophysically reflects membrane raft accumulation, which has potential implications for signaling at ISs.